A new thermostat for real-time price demand response: Cost, comfort and energy impacts of discrete-time control without deadband. (1st October 2015) - Chassin, David P.; Stoustrup, Jakob; Agathoklis, Panajotis; Djilali, Nedjib
Highlights: A new thermostat design that enables reliable aggregate demand response for ancillary services. Performance metrics to rigorously design, monitor, and optimize the demand response performance. Demand response performance objectives utilities can use to deliver load-based ancillary services. A thermostat design that gives consumers control of the demand response services they provide. A numerical method to evaluate the aggregate impact changes to residential thermostat designs. Abstract: Thermostatically controlled electrical loads can provide valuable energy storage and are prime candidates for fast acting demand response (DR) that can be used to mitigate highly variable renewable power generation and limited availability of ramping resources. When conventional thermostats are retrofitted for real-time price DR control, significant control errors can arise, particularly in the form of dispatch control drift. This paper identifies the underlying causes and presents a new residential thermostat design that enables accurate aggregate load control. The new design gives rise to linear time-invariant models of aggregate load control and demand response, which facilitate the design of highly accurate load-based regulation services for electricity interconnections. Detailed simulation and performance studies coupling a residential house and feeder models are presented to show how consumer comfort and cost savings are achieved and how energy use is impacted for cities in three different climatic zones. During peak times, the new thermostat imparts the entire residential load an energy demand elasticity of about 10–25%. Larger demand elasticities could be achieved by extending the control strategy to other residential thermostatic loads. The proposed thermostat design can operate in the real-time distribution capacity auction system and can provide all the benefits associated with transactive systems, and in particular facilitate increased integration of renewable resources.